Fabric testing - Hu, Jinlian; ScienceDirect eBooks (Boca Raton, Fla. : CRC Press ; Cambridge : Woodhead, 2008)
The textile industry is becoming an increasingly competitive environment. Differentiating products by quality is particularly important. Testing can be performed both to improve product quality and achieve compliance to international, regional or retailer specific standards. Fabric testing provides a comprehensive review of the tests available for fabrics. The book begins with introductory chapters which discuss the scope, importance and statistical analysis of fabric testing. The book then reviews various types of fabric tests such as fabric composition testing, physical and mechanical tests, fabric chemical testing, how to test appearance, permeability, comfort and flammability, as well as dyeing and colouring tests and key issues in testing textile samples. With its distinguished editor and international team of contributors Fabric testing is a valuable resource for designers, technologists, quality inspectors and testing institutes in the textile industry. It is also relevant for academics and students within the textile field. Reviews various types of fabric tests including fabric composition and fabric chemical testingDiscusses the scope, significance and statistical analysis of fabric testingAssesses the importance of fabric testing to both product quality and industry standard compliance.
6.6 Light reflectance of a fabric6.7 Conclusions; 6.8 References; 7 Fabric permeability testing; 7.1 Introduction: terms and definitions; 7.2 Aspects of wear comfort; 7.3 Principle of different test methods for fabric permeability properties; 7.4 Types of fabric permeability tests; 7.5 Fabric permeability testing methods: applications; 7.6 Innovative test methods for fabric permeability; 7.7 Conclusions; 7.8 References; 8 Testing for fabric comfort; 8.1 Introduction: defining comfort; 8.2 Evaluating thermal comfort; 8.3 Moisture and comfort; 8.4 Ease of movement.
Print version record.
"The Textile Institute."
Includes bibliographical references.
Elsevier
Keywords: Textile fabrics -- Testing; Textile fabrics -- Mechanical properties; Textile fabrics -- Standards; TECHNOLOGY & ENGINEERING -- Technical & Manufacturing Industries & Trades; TECHNOLOGY & ENGINEERING -- Textiles & Polymers; Textilier; Materialprovning; Textile fabrics -- Standards; Textile fabrics -- Testing; Electronic books